Improving gene editing of CRISPR/Cas9 using the callus-specific promoter pYCE1 in cassava (Manihot esculenta Crantz) - Li, Yuanchao; Bao, Ruxue; Li, Mengtao; Zeng, Changying; Yang, Haojie; Yao, Yuan; Li, Youzhi; Wang, Wenquan; Chen, Xin (Frontiers in Plant Science, 2025)
Previous studies have demonstrated that an appropriate promoter can drive Cas9 transcription in the CRISPR/Cas9 system, which improves the efficiency of gene editing. Here, we identified and characterized callus-specific promoters to enhance gene editing efficiency in cassava. From the transcriptome data of 11 cassava tissues, the gene named YCE1 was identified to exhibit callus-specific expression. Its promoter (pYCE1) could efficiently and specifically drive EGFP transcription in callus tissues. Given that friable embryogenic callus (FECs) is the recipient for genetic transformation in cassava, we replaced the original 35S promoter with pYCE1 to drive Cas9 transcription for improving the CRISPR/Cas9 gene editing system. In single-gene editing, the mutation rate was significantly increased, which reached an overall mutation rate of 95.24% and a homozygous mutation rate of 52.38%, compared with 62.07% and 37.93% with the 35S promoter, respectively. Furthermore, achieving a dual-gene homozygous mutation rate of 64.71% in dual-gene editing demonstrated the high efficiency of pYCE1 in the gene editing application for cassava. These results underscore the potential of pYCE1 to enhance gene editing efficiency in the CRISPR/Cas9 system of cassava. This approach paves the way for advanced gene function research and genetic breeding in cassava.